LANGUAGE RELATIONS AS AN OBJECT OF STATE REGULATION: A RETROSPECTIVE ANALYSIS - Bigari , M. (Pressing Problems of Public Administration, 2019)
Language relations as an object of state regulation is an important component of the broader task of fostering Ukrainian identity, as many scientists consider language to be the basis of this identity. The purpose of the article is to analyze the peculiarities of the language relations regulation on the Ukrainian lands territory based on historical normative documents with determination of the factors that caused the language situation in Ukraine that we have today. An important step in the development of anti-Ukrainian policy was the signing in 1876 of the Yemsky Decree on the prohibition of printing and importing from abroad any Ukrainian-language literature, as well as on the prohibition of Ukrainian stage performances and printing of Ukrainian texts under notes, folk songs etc. Within a short period of activity of the Central Rada and its government, the Ukrainian language has overcome the almost total ban on official communication to the status of a state language. The Ukrainian public republic was defeated, but by the very fact of its existence it demonstrated the desire of Ukrainians for statehood. This could not be ignored by the Bolshevik leaders who went on to create a formally sovereign USSR. They introduced “Ukrainization”, for which the language issue was bound to be raised again. The effects of official “Ukrainization” should not be highly appreciated, but its achievements, which can be attributed to the development of the arts, especially literature, theater, music, cinema, creation of specialized institutions for the study of the humanities, natural and technical sciences, finally the spread of literacy and education at all levels – all in Ukrainian. In 1960-1980 there was a mass closure of Ukrainian schools in the Polish People’s Republic and the Socialist Republic of Romania. And it was not until the end of 1988 that there was a wide debate in the USSR about the need to give Ukrainian the status of a state language. The conceptual foundations for pursuing the policy of the future independent state were set out in the Declaration on State Sovereignty of Ukraine (1990), which declared the state’s commitment to ensuring the national and cultural revival of the Ukrainian people, including the Ukrainian language.